Examining relationships between child skills and potential key components of an evidence-based practice in ASD. (July 2019) - Stahmer, Aubyn C.; Suhrheinrich, Jessica; Roesch, Scott; Zeedyk, Sasha M.; Wang, Tiffany; Chan, Neilson; Lee, Hyon Soo
Abstract: Background: Research in autism spectrum disorders (ASD) has identified a need to understand key components of complex evidence-based practices (EBP). One approach involves examining the relationship between component use and child behavior. Aims: This study provides initial evidence for identifying key components in a specific EBP, Pivotal Response Training (PRT). We examined which components were related to child response and evaluated relationships between provider characteristics, child characteristics and component intensity. Methods: Trained coders reviewed archival videos ( n = 278) for PRT fidelity and child behavior. We completed multi-level regression and latent profile analysis to examine relationships between intensity of individual or combinations of PRT components and child behavior, and moderators of component use. Results: Analyses indicated differential relationships between specific components and child behaviors which may support methods of altering intensity of components to individualize intervention. Profile analysis suggested relatively intensive use of most PRT components, especially antecedent strategies, may maximize child responsivity. Providers with postgraduate education trended toward higher intensity component use. Child characteristics did not moderate use. Implications: Careful examination of key components of ASD interventions may helps clarify the mechanisms of action. Recommendations specific to PRT implementation and use of the methodology for other interventions are discussed.